Black history month: Diversity and the British female suffrage movement - Mukherje, Sumita (The Fawcett Society, 2017)
The fight for the female vote was not solely a British, or a ‘white’ concern, writes historian Sumita Mukherjee.
https://www.fawcettsociety.org.uk/blog/diversity-british-female-suffrage-movement
Keywords: approches et analyses; asie; cours; droits des femmes*; europe; fem1000; féminisme décolonial; inde; mouvements des femmes*; premier cycle; royaume-uni; régions géographiques; suffragettes; thématiques